1991
DOI: 10.1093/ndt/6.3.170
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Uraemic Hyperphosphataemia with Calcium Acetate and Calcium Carbonate: A Comparative Study

Abstract: A comparative study of long-term haemodialysis patients investigated the effects of calcium acetate and calcium carbonate on concentrations of serum phosphate, calcium, and parathyroid hormone. It was demonstrated that both substances led to a significant decrease in phosphate and serum parathyroid hormone. Administration of calcium acetate reduced the serum phosphate concentration in 7 weeks from an initial value of 2.08 +/- 0.53 mmol/l to 1.51 +/- 0.39 mmol/l (P less than 0.01). Following a 1-week wash-out p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…The mean dose required to normal ize serum phosphorus was for CaAC 4.1 ± 0.36 g/day (957 ± 83 mg elemental Ca) and for the CaC0 3 4.01 ± 0.8g/day (1,590 ± 317 mg elemental Ca). This is similar to the re sults obtained by Shaefer et al [22] who needed 1.02 g/day calcium under CaAC and 1.88 g/day under CaCC>3 to con trol the serum phosphorus level. In a similar way Moriniére et al [23] needed 0.65 and 1.3 g/day, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean dose required to normal ize serum phosphorus was for CaAC 4.1 ± 0.36 g/day (957 ± 83 mg elemental Ca) and for the CaC0 3 4.01 ± 0.8g/day (1,590 ± 317 mg elemental Ca). This is similar to the re sults obtained by Shaefer et al [22] who needed 1.02 g/day calcium under CaAC and 1.88 g/day under CaCC>3 to con trol the serum phosphorus level. In a similar way Moriniére et al [23] needed 0.65 and 1.3 g/day, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In the first, Shaefer et al [22] concluded that calcium supplement is reduced to half the dose with CaAC to obtain the same binding effect as compared with CaCC>3; nevertheless, these au thors do not demonstrate a better serum phosphorus con trol or a lower incidence of hypercalcémie episodes. Morinière et al [23], in the other comparative study, ob tained results similar to ours; these authors did not observe any real advantage of CaAC over CaCC>3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Mai et al (37) showed that phosphorus absorption decreased to 40% of the ingested load with calcium carbonate compared with 21.7% with an equivalent amount of calcium acetate. Thus, among patients with ESRD, calcium acetate binds approximately twice the amount of phosphorus per amount of calcium absorbed (38,39). This is believed to be attributable to the increased solubility of calcium acetate in both acid and alkaline solutions in vitro.…”
Section: Calcium Acetatementioning
confidence: 99%